Achieving requisite variety in modeling firms' strategy heterogeneities: Explaining paradoxical firm-market performances - Nagy, G.; Megehee, C.; Woodside, Arch; Laukkanen, T.; Hirvonen, S.; Reijonen, H. (Elsevier, 2017)
This study responds to the view that the crucial problem in strategic management (research) is firm heterogeneity-why firms adopt different strategies and structures, why heterogeneity persists, and why competitors perform differently. The present study applies complexity theory tenets and a "neo-configurational perspective" in proposing firms' complex antecedent conditions affecting firms' complex outcome conditions. The complex outcome conditions include firms with high financial performances in declining markets and firms with low financial performances in growing markets-the study focuses on seemingly paradoxical firm-market outcomes. Based on an analysis of firm strategies and outcomes for separate samples of cross sectional data of 1120 Finish and Hungarian manufacturing firms, this study bridges theory and practice in strategic management of complex firm-orientation configurations and complex firm-performance-capabilities. The study contributes by showing how executives can use "computing-with-words" (CWW) (Zadeh, 1966) for achieving requisite variety in explaining and predicting paradoxical firm performance outcomes.